Anatomical and histological characterization of the filum terminale in dogs - Posporis, Christoforos; Espinosa, Javier; Pumarola, Martí; Ortega, Ester Blasco; Alomar, Jaume; Santifort, Koen; De Decker, Steven; Lam, Karol; Mínguez, Juan José; Álvarez, Patricia; Aige-Gil, Vicente (Frontiers in Veterinary Science, 2025)
The filum terminale (FT) remains poorly characterized in the veterinary literature, limiting understanding of its role in spinal cord and nerve root pathologies such as tethered cord syndrome. This study aimed to establish baseline anatomical and histological features of the FT in neurologically normal dogs. Eight adult canine cadavers euthanized for non-neurological reasons were examined. Dissection was performed via dorsal laminectomy (n = 4) and midline sectioning (n = 4). Histological analysis (n = 4) included hematoxylin and eosin, Klüver-Barrera, Masson’s trichrome, and Verhoeff-Van Gieson stains, alongside immunohistochemistry for neuron-specific enolase, protein gene product 9.5, and glial fibrillary acidic protein. Grossly, the FT was identified as a direct continuation of the conus medullaris within the region of the vertebral canal at L6, extending caudally to form two segments: a cranial portion within the subarachnoid space of the dural sac (filum terminale internum, FTi) and a caudal portion beyond the dural sac, enclosed by the inner dural layer without intervening subarachnoid space (filum terminale externum, FTe). The dural sac terminated at the level of mid-sacrum, with the FTe extending further caudally to insert dorsally between the first and second caudal vertebrae. The FT was accompanied by a ventral artery and vein. Histologically, the FT retained vestigial spinal cord cytoarchitecture, including an irregular, folded central canal with ependymal lining, a subependymal astrocytic layer, gray matter with scattered neurons and glial cells, and peripheral white matter with myelinated axons. The central canal and the neuronal and glial elements progressively diminished caudally as the FT transitioned to collagenous tissue interspersed with sparse residual nerve fibers. Verhoeff-Van Gieson staining revealed minimal elastic fibers within the collagen matrix. This study presents the first comprehensive anatomical and histological characterization of the normal canine FT, establishing baseline reference data to facilitate the identification of pathomorphological alterations associated with disorders involving this structure, such as tethered cord syndrome.